Knowledge Levels and Adolescent Attitudes towards the Implementation of BSE (Breast Self-Examination) in Level I Students - Eka Haryanti; Kamesyworo (Journal of Applied Nursing and Health, 2022)
Background: Breast cancer is a health problem and a cause of death in women. Many women unknowingly have breast cancer and are detected when it is at an advanced stage. The initial effort to detect breast cancer early is with regular BSE examinations carried out independently by women. However, many teenagers do not know about this BSE examination and rarely do it. This study aims to determine the relationship between the level of knowledge and adolescents' attitudes toward implementing BSE in Level I students of the Lahat Nursing Study Program, Poltekkes, Ministry of Health, Palembang in 2021. The study was carried May 21 to June 10, 2021. Methods: This study used a quantitative method with a cross-sectional approach. The population in this study was the first-level student of the Lahat nursing study program, with a total sample of 66 female students using the total sampling technique. Data analysis was carried out univariate and bivariate using the Chi-Square test. Results: The results show that there is a relationship between the levels of knowledge on the implementation of BSE (Breast Self-Examination) with a value (p-value = 0.001), and there is a relationship between attitudes towards the implementation of BSE (Breast Self-Examination) with a value (p-value = 0.001). Conclusion: It is hoped that the Lahat nursing study program will be able to educate about BSE by placing posters about the early detection of breast cancer with BSE and including material about breast cancer and early detection with BSE in the learning materials especially in maternity.